Pengaruh Profitabilitas, Likuiditas, Leverage, Rasio Arus Kas dan Ukuran Perusahaan Terhadap Financial Distress - Purwaningsih, Eny; Safitri, Indah (JAE (JURNAL AKUNTANSI DAN EKONOMI), 2022)
This study aims to identify the factors that influence financial distress conditions, either simultaneously or partially in retail trading sub-sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period. This study uses a type of causal comparative research. The sample in this study is the retail trading sub-sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period using the purposive sampling method. There are 10 companies that meet the sample criteria, so there are 50 financial statements. The factors tested in this study are profitability, liquidity, leverage, cash flow ratio and firm size. The results of the study show that partially the profitability variable (NPM) has a positive effect on financial distress, the liquidity (CR) has a negative effect on financial distress, the leverage variable (DER) has no effect on financial distress, the cash flow ratio (CFR) has a negative effect on financial distress and firm size (FS) has no effect on financial distress. Simultaneously there is an effect of profitability (NPM), liquidity (CR), leverage (DER), cash flow ratio (CFR), and firm size (FS) on financial distress.